Uses of Technology in Upper Secondary Mathematics Education - Hegedus, Stephen; Laborde, Colette; Brady, Corey; Dalton, Sara; Siller, Hans-Stefan; Tabach, Michal; Trgalova, Jana; Moreno-Armella, Luis (ICME-13 Topical Surveys,, 2017)
This survey addresses the use of technology in upper secondary mathematics education from four points of view: theoretical analysis of epistemological and cognitive aspects of activity in new technology mediated learning environments, the changes brought by technology in the interactions between environment, students and teachers, the interrelations between mathematical activities and technology, skills and competencies that must be developed in teacher education. Research shows that the use of some technologies may deeply change the solving processes and contribute to impact the learning processes. The questions are which technologies to choose for which purposes, and how to integrate them, so as to maximize all students’ agency. In particular the role of the teacher in classrooms and the content of teacher education programs are critical for taking full advantage of technology in teaching practice.